Ninteenth century criticism - Houghton, Winifred A. (My University, 1897)
Introduction: Criticism does not flourish in great creative epochs, neither do great works come during any great critical epoch; but rather they alternate. In Greece, all the creative force was spent before anything like criticism, in the shape of Aristotle’s definitions and canons for tragedy appeared. Upon the Greek works or a basis was founded the first epoch of systematic criticism which the world had seen—the Alexandrian era, as it is called. From this period with the advancing ages criticism has grown and flourished until now it is one of the most important factors in the literary world. Matthew Arnold says that “Real criticism is essentially the exercise of curiosity as to ideas on all subjects, for their own sakes, apart from any practical interest they may serve, it obeys an instinct prompting it to try to know the best that is known and thought in the world, irrespectively of practice, politics, and everything of the kind, and to value knowledge and thought as they approach this best, without the intrusion of any other considerations whatever.” This is true of all criticism whether of poetry or of other forms of literature and science.
Citation: Houghton, Winifred A. Ninteenth century criticism. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: Nineteenth century; Criticism; Literature; History; Theses; Manuscripts (documents)